Graphene-embedded broadband tunable metamaterial absorber in terahertz band. (5th December 2019) - Du, Xue-mei; Yan, Feng-ping; Wang, Wei; Tan, Si-yu; Zhang, Lu-na; Bai, Zhuo-ya; Zhou, Hong; Hou, Ya-fei
Abstract: Numerous studies have been conducted to design terahertz broadband metamaterial absorbers for various applications, such as electromagnetic stealth, photodetection, and broadband communications. It remains a hot research topic to design metamaterial absorbers (MAs) to achieve broadband absorption while maintaining a wide range of tunability. Here, we present a novel design of graphene-embedded metamaterial functioning as a broadband tunable absorber based on the field reinforcement effect and plasmon resonance of graphene. With a stacked configuration, the absorptivity of the MA proposed in this paper can be as high as 90% in a wide range of 1.2 THz. By comparative analysis, we exhibit that the MA shows a relatively wider absorption bandwidth than the one without the embedded graphene, which discloses the significance of integrating graphene layer in our design. The detailed numerical calculations of the surface currents and electric field distributions are presented in this paper to better uncover the physical mechanisms of the broadband and multi-band absorption. Moreover, further numerical calculations show that the designed MA also demonstrates several other excellent properties, such as tunability, polarization insensitivity, incident angle insensitivity and outstanding structural parameters tolerance. The proposed graphene-embedded MA can be used in various promising applications, like smart sensors, broadband absorber and imaging devices.